Sex differences in predictability of some measures of college achievement from the college entrance test and/or some measures of high school achievement - Gumban, Remigio S. (Philippine Journal of Psychology, 1972)
Tests of significance of the hypotheses that the predictabilities of college academic criteria (viz., subject-area averages in English, Mathematics, and Social Science, and; an overall measure, defined as average of the subject-area measures) arc equal for male and female "populations" of college freshmen are presented. The findings are as follows: (1) Non-significant sex differences in predictability of the college overall measure, and subject-area average in Social Science when predicted from (a) high school subject-area averages, (b) CET subtest scores, (c) combination of the high school and CET variables, and (d) overall measures in high school (i.e., average of the subject-area averages) and the CET; (2) Significant sex differences in predictabilities of subject-area average in Mathematics in all four prediction schemes above; (3) Significant sex differences in predictability of subject- area average in English in three prediction schemes, viz., (b)-(d) above. Discussions on (1) the "fidelity" of single measures of initial college academic performance, and (2) the implications of the results for admissions purposes arc also presented.